A non-fullerene electron acceptor modified by thiophene-2-carbonitrile for solution-processed organic solar cells. Issue 10 (15th February 2016) - Li, Shuixing; Yan, Jielin; Li, Chang-Zhi; Liu, Feng; Shi, Minmin; Chen, Hongzheng; Russell, Thomas P.
Abstract : An effective strategy to obtain a non-fullerene acceptor with good absorption and high electron mobility by introducing thiophene-2-carbonitrile groups. Abstract : Effective electron acceptor materials usually have a deep lowest unoccupied molecular orbital (LUMO) energy level that can split excitons and generate current. A non-fullerene electron acceptor (F8-DPPTCN) was developed, using fluorene as the core with arms of diketopyrrolopyrrole (DPP) having thiophene-2-carbonitrile as the terminal units. The new molecule had a LUMO of −3.65 eV and a narrow bandgap (Eg ) of 1.66 eV, owing to the electronegativity of the thiophene-2-carbonitrile group and its conjugation with DPP units. Organic solar cells (OSCs) with F8-DPPTCN as the acceptor and poly(3-hexylthiophene) (P3HT) as the donor were fabricated. A power conversion efficiency (PCE) of 2.37% was obtained with an open-circuit voltage ( V oc ) of 0.97 V, a short-circuit current ( J sc ) of 6.25 mA cm −2, and a fill factor (FF) of 0.39. Structural characterization showed that P3HT and F8-DPPTCN were kinetically trapped in a weakly separated state whereas thermal annealing led to the crystallization of P3HT and the formation of a network structure with a mesh-size of several hundred nanometers. When a solvent additive, diiodooctane, was used and the mixture was thermally annealed, both P3HT and F8-DPPTCN crystallized and a multi-length scale network was formed. Though the PCEs were low, the changes in the PCE could be correlated with the morphological changes, opening pathways to increase performance further.